2010
DOI: 10.1002/adma.200902096
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Storage in Metal–Organic Frameworks

Abstract: Metal–organic frameworks (MOFs) are highly attractive materials because of their ultra‐high surface areas, simple preparation approaches, designable structures, and potential applications. In the past several years, MOFs have attracted worldwide attention in the area of hydrogen energy, particularly for hydrogen storage. In this review, the recent progress of hydrogen storage in MOFs is presented. The relationships between hydrogen capacities and structures of MOFs are evaluated, with emphasis on the roles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
178
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(182 citation statements)
references
References 121 publications
(238 reference statements)
1
178
0
3
Order By: Relevance
“…MOF are nanoporous, crystalline materials that consist of metal ions that are connected by organic linkers. [70][71][72][73][74][75] By varying the metal ion or linker, various sizes and shapes of channels or cavities can be obtained. 76 The interest in these materials first appeared after the theoretical paper by K. Zagorodniy and co-authors, who calculated the dielectric constant of a series of MOF based on Zn 4 O(CO 2 ) 4 units connected by different organic linkers and found that all the investigated MOF have k-values below 2.0 with good mechanical properties.…”
Section: Low-k Dielectrics For Future Technology Nodesmentioning
confidence: 99%
“…MOF are nanoporous, crystalline materials that consist of metal ions that are connected by organic linkers. [70][71][72][73][74][75] By varying the metal ion or linker, various sizes and shapes of channels or cavities can be obtained. 76 The interest in these materials first appeared after the theoretical paper by K. Zagorodniy and co-authors, who calculated the dielectric constant of a series of MOF based on Zn 4 O(CO 2 ) 4 units connected by different organic linkers and found that all the investigated MOF have k-values below 2.0 with good mechanical properties.…”
Section: Low-k Dielectrics For Future Technology Nodesmentioning
confidence: 99%
“…The main obstacle to use hydrogen economy in daily life is to store hydrogen as an energy carrier, safely and economically [2][3]. In order to store hydrogen, compressed and liquid gas systems [4] have been being used but for safely and more profitable storage there are many choices such as, metal hydrides [5], carbon nanotubes [6][7], metal organic frameworks (MOFs) [8] which are needed to be improved. Some target values are set for storing acceptable amount of hydrogen to use in portable systems by US DOE (4.5 wt.…”
mentioning
confidence: 99%
“…17 In particular, MOF-5 has been extensively investigated for H 2 storage applications in fuel cells. 18 One strategy is to increase the complexity of the crystals by producing crystals with a hierarchical structure and a high crystal ordering.…”
Section: Introductionmentioning
confidence: 99%